The Continuity of Walisongo's Islamic Propagation (Da'wah): Religious Faculties at State Islamic Universities (UIN) in Indonesia - Jejen Musfah (Jurnal Hikmatuna, 2017)
"The Decline of Muslim Numbers and the Waning Interest in Religious Studies: A Paradox for State Islamic Universities (Universitas Islam Negeri — UIN), Including One Named Walisongo (Referring to Nine Medieval Saints Who Spread Islam in Java). The Islamic Propagation Efforts of Walisongo, Aimed at Islamizing the Javanese Region, Producing 'Ulama Cadres, and Establishing an Islamic Society, Have Seen a Decrease. This Study Aims to Analyze the Reasons for Students' Low Interest in Religious Faculties at UINs and Connect Them to the Spirit of Walisongo's Endeavors. The Study Utilizes a Literature Research Method with a Qualitative Approach, without Quantitative Data Calculation. The Study Concludes that the Existence of Religious Faculties at UINs Is in Line with Walisongo's Objective of Spreading Islam through Educational Institutions. The Religious Faculties, Seen as a Continuation of Walisongo's Struggle in Propagating Islam, Comprise Four Faculties: Adab, Ushuluddin, Syarī'ah, and Da'wah. In the Case of UIN Jakarta, There is a Faculty of Dirāsāt Islamiyyah, Collaborating with Al-Azhar University in Cairo. While Religious Faculties Experienced a Golden Age during the IAIN (Institute of Islamic Studies) Period, They Have Been Diminishing in the UIN Period. The Decline is Evident in the Decreasing Number of Students, Especially in Comparison to the Enrollment Numbers of Secular Faculties at UINs."